Tindak Tutur Netizen Pada Kontroversi Kasus Bunuh Diri Anak Sd Di NTT - Kusmariati Kusmariati; Melyanty Nababan; Melinda Maria Sitanggang; Irfansyah Barus; Yuni Tamba; Herning Puspitarini; Oky Fardian Gafari (CV. SINAR HOWUHOWU, 2026)
This article investigates linguistic phenomena in digital spaces arising as a response to a humanitarian tragedy intersecting with controversial public policy. The primary focus of this research is the analysis of netizen speech acts on the social media platform X (formerly Twitter) following the suicide of a fourth-grade elementary student, YBS, in Ngada Regency, East Nusa Tenggara (NTT) in January 2026. This tragedy became a national discourse as it was triggered by the victim's inability to purchase stationery, amidst a heated debate regarding the allocation of the IDR 335 trillion Free Nutritious Meal (MBG) budget, which consumes a significant portion of education funds in the 2026 State Budget. Utilizing a critical pragmatic approach, this research aims to identify types of illocutionary acts, their pragmatic functions, and the politeness and impoliteness strategies employed as instruments of social criticism. The research method is qualitative descriptive, using the non-participatory observation technique (SBLC) on 47 netizen utterances. Findings indicate a dominance of expressive (38.3%) and directive (34.0%) speech acts, reflecting an escalation from collective emotion into structured political demands. This study confirms that social media has transformed into a digital arena where linguistic power is exercised to dismantle structural injustice and demand state accountability for fundamental educational rights.